Co-chemotherapy effect of the extract of Hibiscus sabdariffa and cisplatin against apoptosis and anti-proliferation on T47d and Vero cells - Citra Ariani Edityaningrum; Amanda Khairurrizki; Laela Hayu Nurani; Moch Saiful Bachri; Sapto Yuliani, Dwi Utami; Kintoko; Nurkhasanah; Lalu Muhammad Irham; Zainul Amiruddin Zakaria (Faculty of Pharmacy, University of Benin, 2024)
The use of cisplatin as a breast cancer chemotherapy agent has side effects, one of which is toxicity to normal cells. Therefore, this study aimed to use Hibiscus sabdariffa extract (HSE) to promote cytotoxic prevention. Several active compounds such as anthocyanin, protocatechuic acid, and hydroxyl citric acid compounds in HSE have cytotoxic activities. Combining cisplatin and the extract of Hibiscus sabdariffa (HSE) as a co-chemotherapy agent reduces the dose of cisplatin. It was discovered that HSE and cisplatin had cytotoxic effects on T47D cells with IC50 values of 32.3 ± 2.15 μg/mL and 6.64 ± 0.68 μg/mL, respectively. Selectivity assay on Vero cells resulted in SI values of 52.84 for HSE and 1220.7 for cisplatin. Anti-proliferation test on control cells indicated a doubling time value of 55.74 ± 0.55 h, while HSE at concentrations of 32.3 µg/mL,16.15 µg/mL, and 8.08 µg/mL didn't indicate any doubling time value. Based on this study, we found that the combination of 16.15 µg/mL of HSE and 3.32 µg/mL of cisplatin had a strong synergistic effect with a Combination Index (CI) value of 0.002. The mechanism of HSE and cisplatin was identified through the increasing expression of p53 and decreasing expression of Bcl-2.